MENINJAU EFEKTIVITAS PROGRAM PENJAMINAN LPS DALAM MENJAGA STABILITAS DAN KEPERCAYAAN DALAM SISTEM KEUANGAN - muslimin; Katsirin, Khairul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research was conducted to review the effectiveness of the LPS guarantee program in maintaining stability and trust in the financial system in Indonesia. The method used is descriptive-qualitative with secondary data collection from various sources. The results of the study indicate that the LPS guarantee program has been successful in maintaining stability and trust in the financial system, especially in Indonesia, but there are several challenges that need to be overcome in order to increase the program's effectiveness. Policy recommendations that can be implemented include increasing the maximum limit for reimbursement of funds by the LPS, increasing the supervisory mechanism for guaranteed banks, increasing public education about the LPS guarantee program, providing more accurate and transparent data and information, and closer cooperation between LPS and guaranteed banks. With the implementation of these policies, it is expected to increase the effectiveness of the LPS guarantee program and maintain stability and trust in the financial system in Indonesia.